CEO involvement in selecting CAE, internal audit competency and independence, and financial reporting quality - Alzeban, Abdulaziz (Journal of Business Economics and Management, 2018)
The purpose of this study is to explore the argument that Chief Executive Officer (CEO) involvement in the appointment of the Chief Auditing Executive (CAE) is detrimental to efforts to achieve good financial reporting quality (FRQ). The study is original in that to date, this precise link has not been investigated. Data are obtained via survey and annual reports relating to 307 UK companies listed on the London Stock Exchange, and the working capital and discretionary accruals are used as proxies for financial reporting quality. The findings support the contention that the benefits to FRQ of an independent and competent internal audit function are not realized when there is CEO involvement in the appointment of the CAE, since management is able to override IA controls. Indeed, high FRQ is only evident when the CEO is not involved in the appointment. The results are found to be robust after using two different methods of estimation, and carry the implication regulators concerned with FRQ and quality of internal audit function that the CEO should not be party to the appointment of the CAE since this will depress FRQ.